Total reading skills for elementary school students through the reading questioning answering model - Vina Anggia Nastitie Ariawan; Sagi Winoto (Jurnal Prima Edukasia, 2021)
Reading is one aspect of language skills that affects student success in understanding various learning materials. Most students are already able to read, but not all students have good reading skill. Therefore, research related to reading skill still really needs to be done to influence students so they prefer reading activities, especially when learning in schools is less effective because of the corona 19 virus. Thus, students are expected to have positive activities when they learn from home like total reading activity. This study aims to measure the total reading skill of fifth-grade students through the Reading Questioning and Answering model. The research method used an experimental method with a pretest-posttest control group design. The research sample was the fifth-grade students who were randomly selected. This research was carried out with a home visit activity and was conducted online. The data were collected using a reading speed test and a reading comprehension test, while the data analysis used inference statistics. The results showed that the reading speed of the experimental class students was higher than the control class students. Subsequently, the reading comprehension skill of the experimental class students was higher than the control class students. Based on the research findings, the researcher concluded that the RQA Model affects the total reading skill of fifth-grade students